Has job security vanished in large corporations? - Allen, Steven G. 1952-; Clark, Robert L. A.; Schieber, Sylvester J. (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1999)
The prevailing wisdom in media accounts is that job stability has vanished, especially for those in large corporations. Academic studies of job stability have found little difference between the 1990s and earlier decades, but these studies have not been able to focus on large firms. This paper provides the first detailed analysis of job stability in large corporations in the 1990s using a sample of 51 firms that are clients of Watson Wyatt Worldwide. We find that mean tenure and the percentage of employees with 10 or more years of service have actually increased in our sample. Even in large firms with shrinking employment, the odds that a worker would be with the same employer five years later were higher than the same odds for the labor market as a whole. There is no evidence that mid-career employees have been singled out in downsizing decisions; their turnover rate is the same in both growing and downsizing firms. Regression analysis shows that the impact of downsizing is still being borne by the most junior workers and that there is no evidence that rising wage differentials by experience are encouraging firms to substitute junior for senior workers.